A Physiotherapy Treatment Plan for Post-COVID-19 Patients That Improves the FEV1, FVC, and 6-Min Walk Values, and Reduces the Sequelae in 12 Sessions - Ponce-Campos, Silvia Denise; Díaz, Juan Manuel; Moreno-Agundis, Daniela; González-Delgado, Ana Laura; Andrade-Lozano, Paulina; Avelar-González, Francisco Javier; Hernández-Cuellar, Eduardo; Torres-Flores, Fernando (Frontiers in Rehabilitation Sciences, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causal agent of Coronavirus disease 2019 (COVID-19), a pandemic disease declared in 2020. The clinical manifestations of this pathology are heterogeneous including fever, cough, dyspnea, anosmia, headache, fatigue, taste dysfunction, among others. Survivors of COVID-19 have demonstrated several persistent symptoms derived from its multisystemic physiopathology. These symptoms can be fatigue, dyspnea, chest pain, dry and productive cough, respiratory insufficiency, and psychoemotional disturbance. To reduce and recover from the post-COVID-19 sequelae is fundamental an early and multifactorial medical treatment. Integral post-COVID-19 physiotherapy is a tool to reduce dyspnea, improve lung capacity, decrease psychoemotional alterations, as well as increase the muscle strength affected by this disease. Thus, the aim of this study was to establish a novel physiotherapeutic plan for post-COVID-19 patients, evaluating the effect of this treatment in the reduction of the sequelae in terms of lung capacity, cardio-respiratory, and muscular strength improvements. This was a cross-sectional study in which a protocol of 12 sessions in 4 weeks of physiotherapy was implemented in the patients enrolled. We conducted a medical assessment, an interview, a DASS-21 test, a spirometry, a six-minute walk test, and a hand dynamometer test to evaluate the post-COVID condition of patients before and after the sessions. A total of 42 patients participated in the program. Results of this work showed a decrease of around 50% of post-COVID-19 sequelae and an improvement in the psychoemotional status of patients. Also, we observed an increase of 7.16% in the FEV1 value and 7.56% for FVC. In addition, the maximal functional capacity increased by 0.577 METs, the six-minute walk test performance increased by 13%, and the SpO2 improved by 1.40%. Finally, the handgrip strength test showed an improvement in the left hand and right hand of 2.90 Kg and 2.24 Kg, respectively. We developed this study to propose a novel methodology to provide information for better treatment and management of post-COVID-19 patients.